2020
DOI: 10.3390/biom10020267
|View full text |Cite
|
Sign up to set email alerts
|

Application of Water Treated with Low-Temperature Low-Pressure Glow Plasma for Quality Improvement of Barley and Malt

Abstract: The aim of this study is to determine the quality of water treated with low-temperature, low-pressure glow plasma, either in the air or under nitrogen, in order to obtain high-quality brewer's malt. To this end, plasma-treated spring water was used for barley grain soaking. In two-row spring barley grain, the procedure provided significantly higher water uptake capacity and grain sensitivity to water, as well as energy and germination capacity. The resulting malt showed improved moisture and 1000-grain mass. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…In a recent study conducted by Pater et al. (2020), steeping water treated with low pressure glow plasma and low temperature in the air or under nitrogen had been observed to improve the malting process, resulting in good quality malt. Once the steeping process is complete, the grain should have attained high moisture levels with a high (%) chit count, which is a white colored visible protrusion of the growing cotyledon/rootlet from the embryo of the grain.…”
Section: The Malting Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study conducted by Pater et al. (2020), steeping water treated with low pressure glow plasma and low temperature in the air or under nitrogen had been observed to improve the malting process, resulting in good quality malt. Once the steeping process is complete, the grain should have attained high moisture levels with a high (%) chit count, which is a white colored visible protrusion of the growing cotyledon/rootlet from the embryo of the grain.…”
Section: The Malting Processmentioning
confidence: 99%
“…Recently, treatment with strong oxidants; Ozone (O 3 ) and hydrogen peroxide (H 2 O 2 ) after 2 hr of first and second steeping were reported to activate hydrolytic enzymes to different levels by inducing the gene expression of abscisic acid (ABA) catabolism (ABA8'OH) and GA biosynthesis (GA20ox1) without contributing any unwanted residues in the malt (Ma et al, 2020). In a recent study conducted by Pater et al (2020), steeping water treated with low pressure glow plasma and low temperature in the air or under nitrogen had been observed to improve the malting process, resulting in good quality malt. Once the steeping process is complete, the grain should have attained high moisture levels with a high (%) chit count, which is a white colored visible protrusion of the growing cotyledon/rootlet from the embryo of the grain.…”
Section: Steepingmentioning
confidence: 99%
“…Murawski et al described benefits of cryopreservation of ram [29] and boar [30] semen in GP-treated water. The barley malt quality could be improved when GP-treated water was applied [31]. Watering peppermint with GP-treated water provided fascinating results [32].…”
Section: Introductionmentioning
confidence: 99%
“…LPGPA stimulate reproduction and pathogenicity of entomopathogenic fungi employed as biopesticides [41]. Similarly, fermentative microorganisms are stimulated by LPGPA, providing quality improvement of brewery barley and malt [42]. Murawski et al [43] and Szymanowicz et al [44] demonstrated successful application of LPGPA in animal breeding.…”
Section: Introductionmentioning
confidence: 99%